Synthesis, Crystal Structure and Fluorescent Properties of Dinuclear Zinc Complex - Bi, Chenglu; Li, Weihua; Lu, Hui; Zhang, Hui; Sun, Jianhua (Asian Journal of Chemistry, 2014)
A dinuclear zinc complex [Zn2(qnal)2(CH3COO)2] (Hqnal: N-(8'-quinolyl)-2-hydroxy-1-naphthaldimine) was synthesized and characterized by X-ray crystallography. The complex crystallizes in monoclinic system, space group C2/c with a = 40.00(3), b = 7.690(5), c = 27.492(16) Å, b = 120.446(11)°, V = 17290(8) Å3, Z = 8. Dc = 1.537 g/cm3, Mr = 843.48, F(000) = 3456, μ(MoKa) = 1.374 mm-1, S = 1.033, R = 0.0403 and wR = 0.1049 for 4454 observed reflections (I > 2s(I)). It exhibits a 3D supramolecular architecture constructing by p-p stacking interactions between quinolyl and naphthyl rings and shows luminescent property in the yellow region.